Conocimientos de los estudiantes universitarios del Colegio Mayor de Antioquia, Medellín, acerca del Papilomavirus humano (2003)
ABSTRACT: Human Papillomavirus (HPV) is the most common sexually transmitted disease in North America. It is obvious that prevention of HPV infections could have an impact on health since this strategy not only would decrease cervical cancer mortality, but it would also reduce the incidence of benign HPV infections such as genital warts. A questionnaire was administered to 146 students in order to evaluate the knowledge and practice that college students from Colegio Mayor de Antioquia have about HPV transmission and associated diseases. As a conclusion, the results of the study show that college students have scarce knowledge about HPV transmission, and an educational intervention could help to increase the awareness that this population have about the role of sexually transmitted diseases and could increase their interest to practice in intervention strategies aimed to prevent HPV transmission. Acquisition of such knowledge could decrease mortality from cervical cancer.